META-ANALYSIS OF THE EFFECT OF LEARNING CYCLE 5E MODEL ON PHYSICS LEARNING - Salam, Salam; Prasetyo, Zuhdan Kun; Mundilarto, Mundilarto; Kuswanto, Heru; Putri, Santri Adi (EDUSAINS, 2024)
Along with the rapid development of science and technology, education is increasing. The improvement of education has encouraged the development of learning methods, techniques, approaches and models that allow students to play an active role in constructing their knowledge. One of them is the 5E learning cycle model.  This study aims to analyse the effect of the 5E learning cycle model on physics learning in terms of education level, grade level, research type, subject matter and learning needs. The method used is a quantitative meta-analysis of SINTA accredited national articles, proceedings and international articles with the latest ten years, namely 2013-2023. Data analysis using effect size. The results of the analysis show that overall the learning cycle 5E model has an effect on physics learning with a high effect interpretation. Therefore, the learning cycle 5E model as a whole can improve students' learning achievement and can be used as an alternative in learning, especially physics. Thus, students can learn actively, effectively and can develop their creativity in solving problems. Thus, the 5E learning cycle model is very influential and effective in learning in general, especially in physics learning and can be applied to 21st century skills.